Multifunctional nanoparticles in endodontics: applications, challenges, and future directions - Una Ivković; Catalina Moreno-Rabié; Arn Mignon; Mostafa EzEldeen; Reinhilde Jacobs (Discover Nano)
Abstract Nanoparticles are emerging as transformative agents in endodontics, addressing challenges in treating the dentin-pulp complex. This scoping review aims to explore multifunctional applications of nanoparticles in endodontics, with a focus on their roles in promoting tissue regeneration through therapeutic effects, enhancing material properties, and serving a carrier function. Following PRISMA-Scoping Review guidelines, a comprehensive literature search was conducted across Web of Science, PubMed, and Scopus. A total of 490 articles were initially identified, of which 92 met the preliminary eligibility criteria. Following full-text screening, 70 studies were included in the qualitative synthesis. Key findings from both in vitro and in vivo studies are summarized in tabular form. Results reveal a notable imbalance in the types of nanomaterials studied: inorganic nanomaterials were reported in 77% of the studies, while only 23% investigated organic nanomaterials. Despite their lower representation, organic nanomaterials demonstrated considerable relevance. Chitosan was reported in 29% of the carrier studies, while extracellular vesicles were featured in 22% of the therapeutic applications. Among inorganic materials, bioactive glass was frequently reported, appearing in 31% of enhancer-related studies, 26% of therapeutic studies, and 13% of those investigating carrier functions. The end applications of these nanoparticles were in 69% of the studies either (direct) pulp capping or root canal filling, highlighting the need for innovative materials in these applications. Regarding experimental models, 75% of the studies conducted in vitro research on relevant cell lines, while 25% employed animal models. Of those 25% in vivo studies, 18% also reported in vitro findings. Nanoparticles hold significant promise for transforming endodontics, offering enhanced antibacterial efficacy and bioactivity while addressing critical limitations of conventional materials. However, challenges remain regarding their long-term biocompatibility, scalability, and integration into clinical workflows. This review emphasizes the need for translational research to bridge the gap between laboratory innovations and clinical practice. Graphical abstract